PERLINDUNGAN MEREK DAGANG: Studi Kasus Penindakan Pidana Terhadap Produk Palsu Dan Bajakan Di Kabupaten Cianjur - Piki Rohmatuloh; Mochamad Rif’at Denasetya; Muhammad Azaria Kanigara Persada; Nurulloh Misbahul Ma’ruf; Novandio Satria Ramadhan (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to analyze the legal mechanisms against trademark violations, implementation challenges, and strategies to strengthen trademark protection in this area. The research employs an empirical juridical method that combines normative analysis of Law Number 20 of 2016 concerning Trademarks and Geographical Indications with empirical studies through in-depth interviews and field observations. Data were collected from a literature review of legal regulations and interviews with law enforcement officers, trademark owners, and business actors in Cianjur. The findings reveal that although national regulations provide an adequate legal framework, their implementation at the local level faces obstacles such as low public legal awareness, weak supervision, and the complexity of counterfeit product distribution. Cases like the counterfeit fertilizer factory in Ciranjang highlight the need to enhance the capacity of law enforcement officers and strengthen inter-agency coordination. Additionally, digitizing the trademark registration and reporting processes, as well as educating the public, are vital solutions to improve the effectiveness of trademark protection. This study underscores the importance of synergy among the government, law enforcement, and society in reinforcing trademark protection.